EFEKTIVITAS VARIASI WAKTU KONTAK SINAR UV-C TERHADAP PENURUNAN BAKTERI COLIFORM PADA AIR MINUM DI PT. X (Politeknik Kesehatan Kemenkes Bandung, 2021)
The purpose of the study was to find out the difference in UV-C contact time against the decrease in coliform bacteria in drinking water. The provision of drinking water in PT. X is sourced from artesian wells. The sample population is the production room of PT. X. Sampling technique in the form of grab sampling with a sample size of 2.4 L. Data collection tools use the Most Probable Number (MPN) to calculate coliforms. Data collection techniques by checking bacteria in the laboratory. In the test results obtained the results of the number of bacteria that is 2 x 103 CFU/100 ml sample. According to PERMENKES RI No. 492 of 2010 on Drinking Water Quality Requirements, drinking water requirements for coliform bacteria numbers are 0 CFU/100 ml of samples. This type of research experiments with post-test design with control. The results of the examination of coliform bacteria in drinking water before passing exposure to disinfection of ultraviolet light (UV-C) obtained results of more than 330 CFU/100 ml, after passing exposure to disinfection of ultraviolet light (UV-C) obtained results ranging from 0 - 12 CFU / 100 ml. Analysis of data using Kruskal Wallis found that P value (Significant) is <0.001 where the figure < 0.05 then Ho was rejected and Ha accepted so that it can be concluded there is a significant difference between the variation in the contact time of exposure to disinfection of ultraviolet light to the decrease in coliform bacteria in drinking water.